Women in contemporary Mexican politics - Rodríguez, Victoria Elizabeth, 1954- (University of Texas Press, 2003)
Since the mid-1980s, a dramatic opening in Mexico's political and electoral processes, combined with the growth of a new civic culture, has created unprecedented opportunities for women and other previously repressed or ignored groups to participate in the political life of the nation. In this book, Victoria Rodriguez offers a comprehensive analysis of how Mexican women have taken advantage of new opportunities to participate in the political process through elected and appointed office, nongovernmental organizations and grassroots activism. Drawing on scores of interviews with politically active women conducted since 1994, Rodriguez looks at Mexican women's political participation from a variety of angles. She analyzes the factors that have increased women's political activity: from the women's movement, to the economic crises of the 1980s and 1990s, to increasing democratization, to the victory of Vicente Fox in the 2000 presidential election. She maps out the pathways that women have used to gain access to public life and also the roadblocks that continue to limit women's participation in politics, especially at higher levels of government.